2019
DOI: 10.1186/s13046-019-1264-2
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib and Temozolomide combination inhibits tumorigenesis by targeting EGFRvIII-cMet signaling in glioblastoma cells

Abstract: Background Glioblastoma (GBM) is an aggressive brain tumor with universal recurrence and poor prognosis. The recurrence is largely driven by chemoradiation resistant cancer stem cells (CSCs). Epidermal growth factor receptor (EGFR) and its mutant EGFRvIII are amplified in ~ 60% and ~ 30% of GBM patients, respectively; however, therapies targeting EGFR have failed to improve disease outcome. EGFRvIII-mediated cross-activation of tyrosine kinase receptor, cMET, regulates GBM CSC maintenance and prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 69 publications
2
75
0
1
Order By: Relevance
“…Aberrant EGFR expression mediates resistance to chemotherapy and radiotherapy through evoking anti‐apoptotic signaling 25,26 . Many preclinical and clinical studies indicated suppression of EGFR activation by EGFR inhibitors enhances anti‐glioblastoma efficacy of chemotherapy or radiotherapy 27,28 …”
Section: Discussionmentioning
confidence: 99%
“…Aberrant EGFR expression mediates resistance to chemotherapy and radiotherapy through evoking anti‐apoptotic signaling 25,26 . Many preclinical and clinical studies indicated suppression of EGFR activation by EGFR inhibitors enhances anti‐glioblastoma efficacy of chemotherapy or radiotherapy 27,28 …”
Section: Discussionmentioning
confidence: 99%
“…Stem cell or non-stem cell populations were isolated by using ATP-binding cassette inhibitor (verapamil) and DNA staining dye (Hoechst 33342) [17]. Both parental and MUC5AC KO clones were seeded (approximately 1 × 10 6 cells) and treated with verapamil (75 μM).…”
Section: Isolation Of Side or Stem Cell Populationmentioning
confidence: 99%
“…Reports from in vitro studies conducted on EGFR vIII -expressing cell lines tend to be contradictory. Some results indicate EGFR vIII sensitivity, while the others demonstrate that EGFR vIII , in contrast to EGFR WT , appears to be relatively resistant to EGFR-TKIs [87]. By now, several TKI-involving clinical trials on glioblastoma were completed or terminated, however still without any significant patients' benefits [65,72,77,88,178,[184][185][186][187][188].…”
Section: Journal Of Oncologymentioning
confidence: 99%